2017
DOI: 10.24263/2304-974x-2017-6-2-10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seasonal Environmental Changes on The Biochemical Composition of Sea Cucumber (Holothuria tubulosa Gmelin, 1791) in The Dardanelles Strait

Abstract: Keywords:Biochemical Sea cucumber Holothuria tubulosa Dardanelles Strait

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Similarly, Cakli et al, determined that raw sea cucumbers ( H. tubulosa ) contained 87% moisture, 8% protein, and 0.2% fat. It was observed that sea cucumbers of commercial value existing in Turkish seas have a high protein and low fat content and can be regarded as a dietetic food in terms of nutrition (Culha et al, ). Similar results have been obtained in studies conducted on Actinopyga mauritiana , Holothuria arenicola , Holothuria leucospilota , Holothuria scabra , Holothuria parva , Holothuria spinifera , Stichopus naso, and Thelenota anax (Haider, Sultana, Jamil, Tarar, & Afzal, ; Ketharani & Sivashanthini, ; Salarzadeh et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Cakli et al, determined that raw sea cucumbers ( H. tubulosa ) contained 87% moisture, 8% protein, and 0.2% fat. It was observed that sea cucumbers of commercial value existing in Turkish seas have a high protein and low fat content and can be regarded as a dietetic food in terms of nutrition (Culha et al, ). Similar results have been obtained in studies conducted on Actinopyga mauritiana , Holothuria arenicola , Holothuria leucospilota , Holothuria scabra , Holothuria parva , Holothuria spinifera , Stichopus naso, and Thelenota anax (Haider, Sultana, Jamil, Tarar, & Afzal, ; Ketharani & Sivashanthini, ; Salarzadeh et al, ).…”
Section: Resultsmentioning
confidence: 99%